Player vectors: Characterizing soccer players` playing style from match event streams - Decroos, T.; Davis, J. (European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, 2019/09/16 - 2019/09/20, Würzburg, 2019)
Transfer fees for soccer players are at an all-time high. To make the most of their budget, soccer clubs need to understand the type of players they have and the type of players that are on the market. Current insights in the playing style of players are mostly based on the opinions of human soccer experts such as trainers and scouts. Unfortunately, their opinions are inherently subjective and thus prone to faults. In this paper, we characterize the playing style of a player in a more rigorous, objective and data-driven manner. We characterize the playing style of a player using a so-called `player vector` that can be interpreted both by human experts and machine learning systems. We demonstrate the validity of our approach by retrieving player identities from anonymized event stream data and present a number of use cases related to scouting and monitoring player development in top European competitions.